2021
DOI: 10.1177/0271678x21992622
|View full text |Cite
|
Sign up to set email alerts
|

Lenticulostriate artery combined with neuroimaging markers of cerebral small vessel disease differentiate the pathogenesis of recent subcortical infarction

Abstract: Recent subcortical infarction (RSI) in the lenticulostriate artery (LSA) territory with a non-stenotic middle cerebral artery is a heterogeneous entity. We aimed to investigate the role of LSA combined with neuroimaging markers of cerebral small vessel disease (CSVD) in differentiating the pathogenic subtypes of RSI by whole-brain vessel-wall magnetic resonance imaging (WB-VWI). Fifty-two RSI patients without relevant middle cerebral artery (MCA) stenosis on magnetic resonance angiography were prospectively en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
(60 reference statements)
2
19
0
Order By: Relevance
“… 25 , 26 Until recently, the specific pathological mechanisms underlying CSVD still remained largely unknown, in part because of the lack of effective methods that can technically visualize or image small vessels in vivo. 4 , 25 Although the advances in neuroimaging have provided novel information in CSVD including detailed evaluation of the vessel wall, atherosclerotic plaques within intracranial arteries, 27 , 28 white matter integrity, WMH shape, and the fraction of free water in the drainage area, 29 , 30 , 31 there have been few researches investigating the dynamic vasculature's function of small vessels, such as dCA.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 Until recently, the specific pathological mechanisms underlying CSVD still remained largely unknown, in part because of the lack of effective methods that can technically visualize or image small vessels in vivo. 4 , 25 Although the advances in neuroimaging have provided novel information in CSVD including detailed evaluation of the vessel wall, atherosclerotic plaques within intracranial arteries, 27 , 28 white matter integrity, WMH shape, and the fraction of free water in the drainage area, 29 , 30 , 31 there have been few researches investigating the dynamic vasculature's function of small vessels, such as dCA.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI), three-dimensional time-of-flight MRA (3D-TOF-MRA), susceptibility-weighted image (SWI), and conventional Tl-weighted, T2-weighted, fluid-attenuated inversion recovery (FLAIR) images were obtained as shown in Figure 1 . The detailed parameters of the imaging sequences have been well described in our previous study (Jiang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI), threedimensional time-of-flight MRA (3D-TOF-MRA), susceptibilityweighted image (SWI), and conventional Tl-weighted, T2weighted, fluid-attenuated inversion recovery (FLAIR) images were obtained as shown in Figure 1. The detailed parameters of the imaging sequences have been well described in our previous study (Jiang et al, 2021). All MR images were reviewed and analyzed with commercial software (OsiriX MD, Pixmeo SARL, Bernex, Switzerland) by two experienced readers (SJ and BW) blind to clinical information.…”
Section: Magnetic Resonance Imaging Protocols and Imaging Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that whole-brain HR-MRI is feasible for assess-ing both large-vessel wall lesions and lenticulostriate vasculopathy in a single scan [6]. Using this novel imaging technique to evaluate the spatial relationship between middle cerebral artery (MCA) plaques and the origin of lenticulostriate arteries (LSAs), we appear to be the first group to categorize in vivo LS into BAD-related and CSVD-related LS [45], according to the original pathological descriptions (Fig. 4).…”
Section: Advanced Neuroimagingmentioning
confidence: 99%